Destination Branding Process of Bengkalis Regency as a Cultural Tourism Destination by the Board of Tourism, Culture, Youth and Sports - Ayu Septiana; Yanti Setianti; Wawan Setiawan (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
The existence of tourism development policies that are not supported by integrated communication activities makes tourism problems in Bengkalis Regency increasingly complex. Disparbudpora has made Bengkalis Regency a cultural tourism destination through destination branding. This study aims to determine the destination branding process for Bengkalis Regency by the Board of Tourism, Culture, Youth and Sports (Disparbudpora) as a cultural tourism destination. The research method used is qualitative with a descriptive case study approach. The results of this study indicate that Disparbudpora of Bengkalis Regency introduces cultural tourism destinations by carrying out 5 stages of destination branding. The first stage is market investigation, analysis and strategic recommendation, namely by collecting secondary data, field surveys and data analysis. The two stages of Brand identity development, using the Sembayung logo and the tagline Bengkalis diversity of culture. The three stages of brand launch and introduction are carried out through digital communication and special events which are held annually. The four brand implementations are carried out in accordance with the program set in RIPPARDA 2021-2035. Fifth, Brand monitoring, evaluation and review is carried out directly, through the UPT Tourism and destination managers and Evaluation, a review that discusses the data that has been collected regarding the deficiencies and advantages of destinations.